Chiral Metasurfaces: Metasurface Reconfiguration through Lithium‐Ion Intercalation in a Transition Metal Oxide (Advanced Optical Materials 2/2017). Issue 2 (January 2017) - Zanotto, Simone; Blancato, Alessandra; Buchheit, Annika; Muñoz‐Castro, Marina; Wiemhöfer, Hans‐Dieter; Morichetti, Francesco; Melloni, Andrea
Abstract : Tuning the phase and amplitude response of achiral and chiral metasurfaces is a key operation in optical science and technology, since it lies at the heart of devices like wavefront shapers, beam steerers, and many others. In article number 1600732, the concept of ion intercalation is bridged from the domain of electrochemistry to that of photonics, paving the way for a new class of reconfigurable optical devices, by S. Zanotto and co‐workers.